Penggunaan aplikasi tracker pada materi kinematika dan dampaknya terhadap pencapaian hasil belajar siswa kelas X - Oktriyeni Oktriyeni; Amali Putra (Universitas Negeri Padang, 2019)
Kinematics is a part of physics. It discusses about motion without regard to the external forces which cause the motion. In senior high school, kinematics is divided into three of basic competency. They are straight motion, parabolic motion and circular motion. The important of part for this topic is relation graphs of several magnitudes are often presented. Kinematics graphs are often not thoroughly discussed at school. So most studets can’t analyze the graphs about straight motion and parabolic motion. To overcome this problem, a media are needed that has developed at this time. That is often used in physics learning, especially in motion. Its name is tracker. Tracker is a free video analysis application that can be downloaded using internet. This application was developed by Open Source Physics which is able to analyze the graph of movement of objects through video. Through the use of this applicatio, it is expected that there will be an increase in student learning outcomes